2021
DOI: 10.1590/0102-672020200003e1527
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Tissular Response After Abdominal Wall Repair Using Polypropylene Mesh and Bovine Pericardium Mesh

Abstract: Background: The use of polypropylene meshes for surgical repair of the abdominal wall contributes to a reduction of the of recurrence rates of hernias or defects. However, its intra-abdominal use comes along with the formation of adhesions and several complications. The study and the search for alternative materials, including bovine pericardium, have been regarded as an option for the correction and treatment of resulting hernias with better adaptations and effectiveness. Aim: Evaluating the inflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 12 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Walter de Biase SILVA-NETO 1 , Claudemiro QUIRESE 1 , Eduardo Guimarães Horneaux de MOURA 2 , Fabricio Ferreira COELHO 3 , Paulo HERMAN 3 ABSTRACT -Background: The treatment of choice for patients with schistosomiasis with previous episode of varices is bleeding esophagogastric devascularization and splenectomy (EGDS) in association with postoperative endoscopic therapy. However, studies have shown varices recurrence especially after long-term follow-up.…”
Section: A Queda Da Pressão Portal Após Desvascularização Esofagogást...mentioning
confidence: 99%
See 1 more Smart Citation
“…Walter de Biase SILVA-NETO 1 , Claudemiro QUIRESE 1 , Eduardo Guimarães Horneaux de MOURA 2 , Fabricio Ferreira COELHO 3 , Paulo HERMAN 3 ABSTRACT -Background: The treatment of choice for patients with schistosomiasis with previous episode of varices is bleeding esophagogastric devascularization and splenectomy (EGDS) in association with postoperative endoscopic therapy. However, studies have shown varices recurrence especially after long-term follow-up.…”
Section: A Queda Da Pressão Portal Após Desvascularização Esofagogást...mentioning
confidence: 99%
“…Some authors have dedicated themselves to create risk stratification models to identify these high-risk patients and propose strategies to decrease their incidence 22 . It is well established that the use of mesh drastically increases the success rate of IH repairs and decreases its occurrence when used prophylactically in laparotomies 1,3,6,7,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Walter de Biase SILVA-NETO 1 , Claudemiro QUIRESE 1 , Eduardo Guimarães Horneaux de MOURA 2 , Fabricio Ferreira COELHO 3 , Paulo HERMAN 3 ABSTRACT -Background: The treatment of choice for patients with schistosomiasis with previous episode of varices is bleeding esophagogastric devascularization and splenectomy (EGDS) in association with postoperative endoscopic therapy. However, studies have shown varices recurrence especially after long-term follow-up.…”
Section: A Queda Da Pressão Portal Após Desvascularização Esofagogást...mentioning
confidence: 99%
“…Inguinal hernias can be repaired through open procedures or laparoscopic procedures. Currently, the laparoscopic approach can be transabdominal extraperitoneal (TEP) or transabdominal preperitoneal (TAPP), both of which use mesh and are widely performed 3,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, studies that are related to the use of surgical in the surgery correction of hernias attempted to find the ideal model 1 , 7 , 23 . In this way, less invasive fixation methods were developed, which can be demonstrated by the advent of surgical glue 5 , 11 , 15 .…”
Section: Introductionmentioning
confidence: 99%